Fine, smooth and high-strength artificial stone and preparation method thereof

By optimizing the formula and carbonation and curing process of artificial stone slurry, using CO2 to generate calcium carbonate and magnesium carbonate crystals, combining polyphosphate and silica fume to generate gels, fibers improve toughness, and solving the strength of artificial stone preparation in the prior art in steel slag in the preparative technology and the problem of rough surface, a fine, smooth and high-strength artificial stone is achieved.

CN119241199AInactive Publication Date: 2025-01-03FOSHAN DONGPENG CERAMIC +4
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411373951.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The artificial stone prepared with steel slag in the prior art has poor strength and rough surface, insufficient carbonation, resulting in volume instability and aesthetics problems, and the calcium oxide and magnesium oxide in the steel slag cannot be fully utilized.

Method used

The artificial stone slurry formula includes steel slag, calcium magnesium sand, magnesium bicarbonate, calcium carbonate whiskers, polyphosphate, silica fume and fibers. The rapid dissolution of CO2 during the carbonation and maintenance process is used to form calcium carbonate and magnesium carbonate crystals, combined with Polyphosphate complexes with Ca2+ and Mg2+, and silica fume generates hydrated calcium silicate and hydrated magnesium silicate gels, fibers improve toughness, and calcium carbonate crystals and magnesium carbonate crystals fill pores to increase strength.

Benefits of technology

It realizes fine, smooth and high-strength artificial stone, with compressive strength ≥110MPa and flexural strength ≥19MPa, which solves the problems of insufficient carbonation degree and rough surface of steel slag, and improves the volume stability and aesthetics of artificial stone.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses fine and smooth artificial stone with high strength. The artificial stone is obtained by carbonating, curing and curing artificial stone slurry, the artificial stone slurry is prepared from the following raw materials in parts by mass: 40 to 60 parts of steel slag, 70 to 120 parts of calcium magnesia, 1 to 5 parts of magnesium bicarbonate, 0.01 to 0.05 part of calcium carbonate whisker, 0.01 to 0.03 part of polyphosphate, 2 to 10 parts of silica fume, 1 to 2 parts of fiber and 8 to 10 parts of water. The chemical components of the steel slag comprise silicon dioxide, magnesium oxide and calcium oxide; the mineral components of the steel slag comprise tricalcium silicate, beta-type dicalcium silicate, gamma-type dicalcium silicate, free calcium oxide and free magnesium oxide. The fine, smooth and high-strength artificial stone provided by the invention is fine and smooth in surface and relatively high in strength, and meets actual use requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of artificial stones, and in particular to an artificial stone that is fine, smooth and high in strength and a preparation method thereof. Background Art

[0002] Artificial stone is a decorative material made from raw materials such as cement, admixtures, quartz sand or calcium carbonate through high temperature and high pressure. It not only has the beautiful texture of natural stone, but also has excellent properties such as wear resistance, high temperature resistance and corrosion resistance. It is widely used in many fields such as home decoration, commercial places and medical facilities.

[0003] Steel slag generated in industrial production is a solid waste. Its large accumulation not only occupies precious land resources, but also may cause environmental pollution and other problems. In order to promote resource recycling, reduce production costs and alleviate environmental pressure, researchers have begun to explore new ways to use steel slag to prepare artificial stone. Among them, the chemical components of steel slag include silicon dioxide, magnesium oxide and calcium oxide, etc.; magnesium oxide mainly exists in the form of free calcium oxide, and magnesium oxide mainly exists in the form of free magnesium oxide; at the same time, the chemical component calcium oxide of steel slag can also form tricalcium silicate (C3S), β-type dicalcium silicate (β-C2S), and γ-type dicalcium silicate (γ-C2S) with its component silicon dioxide. In addition, the chemical components calcium oxide and magnesium oxide in steel slag can also form FeO-CaO-MgO-MnO (RO phase) with other chemical components, so that the mineral components in steel slag are mainly tricalcium silicate, β-type dicalcium silicate, γ-type dicalcium silicate, free calcium oxide, free magnesium oxide, FeO-CaO-MgO-MnO solid solution, etc. Since tricalcium silicate, β-type dicalcium silicate, γ-type dicalcium silicate, free calcium oxide and free magnesium oxide in steel slag have certain hydration activity and carbonation activity, it is beneficial to promote the use of steel slag in the preparation of artificial stone.

[0004] However, the prior art of using steel slag to prepare artificial stone has the following defects: (1) It is difficult to carbonate tricalcium silicate, β-type dicalcium silicate, γ-type dicalcium silicate, and Ca in free calcium oxide. 2+ and Mg in free magnesium oxide 2+ Fully participate in the carbonation reaction (i.e. Ca in steel slag 2+ and Mg 2+The dissolution degree is limited), resulting in insufficient carbonation of steel slag, which in turn affects the strength of artificial stone; (3) The free calcium oxide and free magnesium oxide in steel slag have low hydration activity and high content. Their continuous slow hydration in the environment not only causes delayed expansion and cracking of artificial stone, which will bring serious volume stability problems, but also leads to the inability to fully utilize the free calcium oxide and free magnesium oxide in steel slag, affecting the strength of artificial stone; (3) The particle size and shape of steel slag are irregular, and during the carbonation and hydration process, steel slag is easily solidified to form uneven crystals, making the surface of artificial stone relatively rough, affecting the appearance and use effect. That is, the artificial stone made from steel slag in the prior art has poor strength and a relatively rough surface, which is difficult to meet actual use requirements. Summary of the invention

[0005] The purpose of the present invention is to provide an artificial stone which is fine, smooth and high in strength, and which not only has a fine and smooth surface but also has high strength, thus meeting the actual use requirements.

[0006] Another object of the present invention is to provide a method for preparing a fine, smooth and high-strength artificial stone. The preparation method is simple and easy to operate, ensuring that the obtained artificial stone has a compressive strength of ≥110MPa and a flexural strength of ≥19MPa. The surface is not only fine and smooth, but also has high strength.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] A fine, smooth and high-strength artificial stone obtained by carbonation, curing and solidification of artificial stone slurry;

[0009] Calculated by weight, the artificial stone slurry includes the following raw materials: 40-60 parts of steel slag, 70-120 parts of calcium magnesium sand, 1-5 parts of magnesium bicarbonate, 0.01-0.05 parts of calcium carbonate whiskers, 0.01-0.03 parts of polyphosphate, 2-10 parts of silica fume, 1-2 parts of fiber and 8-10 parts of water;

[0010] The chemical components of the steel slag include silicon dioxide, magnesium oxide and calcium oxide; the mineral components of the steel slag include tricalcium silicate, beta-type dicalcium silicate, gamma-type dicalcium silicate, free calcium oxide and free magnesium oxide.

[0011] Furthermore, the particle size of the steel slag is less than 75 μm, and the specific surface area is greater than 350 m 2 / g.

[0012] Furthermore, calculated by mass percentage, the chemical composition of the steel slag includes 12-14% silicon dioxide, 40-45% calcium oxide, 3-5% magnesium oxide, 3-5% aluminum oxide, 20-25% iron oxide, 4-6% manganese oxide, 1-2% titanium dioxide, 0-1% potassium oxide and 2-4% phosphorus pentoxide.

[0013] Furthermore, the fibers include any one or more combinations of polypropylene fibers, polyethylene fibers, polyoxymethylene fibers and polyvinyl alcohol fibers.

[0014] Furthermore, calculated by mass percentage, the calcium-magnesium sand includes 0-30% of Class I sand of 26-40 meshes, 40-60% of Class II sand of 40-70 meshes, 15-30% of Class III sand of 70-120 meshes, and 10-25% of Class IV sand of 120-200 meshes.

[0015] Furthermore, the polyphosphate includes any one of sodium pyrophosphate, potassium pyrophosphate, sodium tripolyphosphate, potassium tripolyphosphate, sodium hexametaphosphate and potassium hexametaphosphate.

[0016] Furthermore, the artificial stone slurry also includes a silane coupling agent;

[0017] Calculated by weight, the artificial stone slurry includes the following raw materials: 40-60 parts of steel slag, 70-120 parts of calcium magnesium sand, 1-5 parts of magnesium bicarbonate, 0.01-0.05 parts of calcium carbonate whiskers, 0.01-0.03 parts of polyphosphate, 2-10 parts of silica fume, 1-2 parts of fiber, 0.01-0.05 parts of silane coupling agent and 8-10 parts of water.

[0018] A method for preparing a fine, smooth and high-strength artificial stone, which is used to prepare the fine, smooth and high-strength artificial stone, comprises the following steps:

[0019] A. dissolving a formula amount of magnesium bicarbonate, calcium carbonate whisker, silica fume and silane coupling agent in a part of the formula amount of water, and stirring evenly to obtain a first mixed material;

[0020] B. uniformly mixing the remaining amount of water and polyphosphate to obtain a second mixture;

[0021] C. After the first mixture, the second mixture, the formula amount of steel slag and calcium magnesium sand are mixed evenly, the formula amount of fiber is added, and the artificial stone slurry is obtained after stirring evenly;

[0022] D. Pour the artificial stone slurry into the mold and press it into shape to obtain the intermediate product;

[0023] E. The intermediate product is subjected to carbonation curing and then solidified to obtain a fine, smooth and high-strength artificial stone, wherein the thickness of the artificial stone is 10 to 40 mm, the compressive strength is ≥110 MPa, and the flexural strength is ≥19 MPa.

[0024] Furthermore, in step E, the carbonation curing temperature is 20-90° C., the curing time is 1-72 h, the curing pressure is 0.1-0.4 MPa, and the purity of CO2 is 50-99.9%.

[0025] Furthermore, in step D, the pressure of the compression molding is 8 to 25 MPa.

[0026] The technical solution provided by the present invention may include the following beneficial effects:

[0027] 1. During carbonation curing, gaseous CO2 quickly dissolves in the slurry to form carbonic acid, which then dissociates to form bicarbonate ions and carbonate ions; calcium hydroxide generated by free calcium oxide in an aqueous environment reacts with bicarbonate ions / carbonate ions to form calcium carbonate crystals, and magnesium hydroxide generated by free magnesium oxide in an aqueous environment reacts with bicarbonate ions / carbonate ions to form magnesium carbonate crystals, so that free calcium oxide and free magnesium oxide in the steel slag are quickly and massively eliminated, thereby not only eliminating the hidden danger of delayed expansion and cracking caused by the slow hydration of free calcium oxide and free magnesium oxide, but also the generated calcium carbonate crystals and magnesium carbonate crystals can improve the strength of artificial stone by filling pores and compacting the matrix. In addition, in an aqueous environment, the mineral components of the steel slag, tricalcium silicate, β-type dicalcium silicate and γ-type dicalcium silicate, can react with bicarbonate ions / carbonate ions to form silica gel, which can better wrap and bond the calcium-magnesium sand aggregate in the artificial stone slurry formula to improve the strength of the artificial stone.

[0028] 2. Polyphosphate as a complexing agent can react with Ca 2+ and Mg 2+ Complexation weakens the Ca-O and Mg-O bonds in the slag mineral components and promotes Ca 2+ and Mg 2+ The dissolution in the slurry makes the Ca in the slag 2+ and Mg 2+ Participate in the carbonation reaction as much as possible, improve its carbonation degree, and thus increase the strength of artificial stone, while also further eliminating problems such as delayed expansion and cracking caused by the slow hydration of free calcium oxide and free magnesium oxide.

[0029] 3. The silicon dioxide in silica fume is tiny spherical and has high reaction activity. It can not only react with calcium hydroxide generated by free calcium oxide, tricalcium silicate, β-type dicalcium silicate and γ-type dicalcium silicate in steel slag in an aqueous environment to form hydrated calcium silicate gel, but also react with magnesium hydroxide generated by free magnesium oxide in an aqueous environment to form hydrated magnesium silicate gel. Hydrated calcium silicate gel and hydrated magnesium silicate gel can better wrap and bond the calcium-magnesium sand aggregate in the artificial stone slurry formula, which is beneficial to improve the strength of artificial stone.

[0030] 4. Magnesium bicarbonate can provide a large amount of bicarbonate ions to promote the Ca in steel slag 2+ and Mg 2+The carbonation reaction solves the technical problem that the silica gel produced in the carbonation process of steel slag easily affects the degree of carbonation, and further improves the strength of artificial stone. In addition, the magnesium ions in magnesium bicarbonate can also react with the silicon dioxide in silica fume to generate hydrated magnesium silicate gel. The hydrated magnesium silicate gel can replace cement as a gelling material, better wrap and bond the calcium and magnesium sand in the artificial stone slurry formula, and improve the strength of artificial stone. DETAILED DESCRIPTION

[0031] The technical solution provides a fine, smooth and high-strength artificial stone obtained by carbonation, curing and solidification of artificial stone slurry;

[0032] Calculated by weight, the artificial stone slurry includes the following raw materials: 40-60 parts of steel slag, 70-120 parts of calcium magnesium sand, 1-5 parts of magnesium bicarbonate, 0.01-0.05 parts of calcium carbonate whiskers, 0.01-0.03 parts of polyphosphate, 2-10 parts of silica fume, 1-2 parts of fiber and 8-10 parts of water;

[0033] The chemical components of the steel slag include silicon dioxide, magnesium oxide and calcium oxide; the mineral components of the steel slag include tricalcium silicate, beta-type dicalcium silicate, gamma-type dicalcium silicate, free calcium oxide and free magnesium oxide.

[0034] In view of the technical problem that the artificial stone obtained by using steel slag in the prior art has poor strength and a rough surface, the present technical solution proposes an artificial stone that is delicate, smooth and high in strength. By designing the proportion of artificial stone slurry and optimizing the raw materials, the artificial stone not only has a delicate and smooth surface, but also has high strength, which meets the actual use needs.

[0035] Specifically, the free calcium oxide and free magnesium oxide in steel slag have low hydration activity and high content. Their continuous slow hydration in the environment not only causes delayed expansion and cracking of artificial stone, bringing serious volume stability problems, but also will lead to the inability to fully utilize the free calcium oxide and free magnesium oxide in the steel slag, affecting the strength of the artificial stone.

[0036] The raw materials of artificial stone slurry in this technical solution include steel slag, calcium magnesium sand, magnesium bicarbonate, calcium carbonate whisker, polyphosphate, silica fume, fiber and water; the chemical composition of steel slag includes silicon dioxide, magnesium oxide and calcium oxide. Firstly, since calcium oxide in steel slag mainly exists in the form of free calcium oxide, magnesium oxide mainly exists in the form of free magnesium oxide, and free calcium oxide reacts in a water environment to form calcium hydroxide, free magnesium oxide reacts in an aqueous environment to form magnesium hydroxide, which increases the alkalinity of the slurry. During carbonation curing, gaseous CO2 quickly dissolves in the slurry to form carbonic acid, which then dissociates to form bicarbonate ions and carbonate ions; calcium hydroxide generated by free calcium oxide in an aqueous environment reacts with bicarbonate ions / carbonate ions to form calcium carbonate crystals, and magnesium hydroxide generated by free magnesium oxide in an aqueous environment reacts with bicarbonate ions / carbonate ions to form magnesium carbonate crystals, so that free calcium oxide and free magnesium oxide in the steel slag are quickly and massively eliminated, thereby not only eliminating the hidden danger of delayed expansion and cracking caused by the slow hydration of free calcium oxide and free magnesium oxide, but also the generated calcium carbonate crystals and magnesium carbonate crystals can improve the strength of artificial stone by filling pores and compacting the matrix. In addition, in an aqueous environment, the mineral components of the steel slag, tricalcium silicate, β-type dicalcium silicate and γ-type dicalcium silicate, can react with bicarbonate ions / carbonate ions to form silica gel, which can better wrap and bond the calcium-magnesium sand aggregate in the artificial stone slurry formula to improve the strength of the artificial stone.

[0037] In addition, although carbonation can make tricalcium silicate, β-type dicalcium silicate, γ-type dicalcium silicate, Ca in free calcium oxide 2+ and free magnesium oxide Mg 2+ A large amount of Ca in the slag participates in the reaction. 2+ and Mg 2+ The dissolution degree is limited, and it is still difficult to fully participate in the carbonation reaction, resulting in insufficient carbonation of the steel slag. The strength of the obtained artificial stone is limited and it is difficult to meet the actual use requirements. 2+ and Mg 2+ As much as possible, the technical solution specifically adds polyphosphate to the artificial stone slurry formula. Polyphosphate acts as a complexing agent, which can react with Ca 2+ and Mg 2+ Complexation weakens the Ca-O and Mg-O bonds in the slag mineral components and promotes Ca 2+ and Mg 2+ The dissolution in the slurry makes the Ca in the slag 2+ and Mg 2+ Participate in the carbonation reaction as much as possible, improve its carbonation degree, and thus increase the strength of artificial stone, while also further eliminating problems such as delayed expansion and cracking caused by the slow hydration of free calcium oxide and free magnesium oxide.

[0038] Furthermore, in order to increase the Ca content in steel slag 2+ and Mg 2+ The dissolution degree can be increased, thereby further improving the strength of the artificial stone. The technical solution adds silica fume to the artificial stone slurry formula. The silicon dioxide in the silica fume is in a tiny spherical shape and has a high reaction activity. It can not only react with the calcium hydroxide generated by free calcium oxide, tricalcium silicate, β-type dicalcium silicate and γ-type dicalcium silicate in the steel slag in an aqueous environment to generate hydrated calcium silicate gel, but also react with the magnesium hydroxide generated by free magnesium oxide in an aqueous environment to generate hydrated magnesium silicate gel. The hydrated calcium silicate gel and the hydrated magnesium silicate gel can better wrap and bond the calcium-magnesium sand aggregate in the artificial stone slurry formula, which is beneficial to improving the strength of the artificial stone.

[0039] Secondly, during the carbonation curing process, the carbonation of steel slag will produce silica gel, which easily hinders the diffusion of bicarbonate ions / carbonate ions, resulting in the Ca in some steel slag. 2+ and Mg 2+ It is difficult to react with bicarbonate ions / carbonate ions for carbonation. However, in the present technical solution, magnesium bicarbonate is also added to the slurry formula, which can provide a large amount of bicarbonate ions and promote the Ca in the steel slag. 2+ and Mg 2+ The carbonation reaction solves the technical problem that the silica gel produced in the carbonation process of steel slag easily affects the degree of carbonation, and further improves the strength of artificial stone. In addition, the magnesium ions in magnesium bicarbonate can also react with the silicon dioxide in silica fume to generate hydrated magnesium silicate gel. The hydrated magnesium silicate gel can replace cement as a gelling material, better wrap and bond the calcium and magnesium sand in the artificial stone slurry formula, and improve the strength of artificial stone.

[0040] It should be noted that magnesium bicarbonate is easily decomposed to form magnesium carbonate precipitate and magnesium hydroxide precipitate in an alkaline environment, which reduces the solubility of magnesium ions in the solution and is not conducive to the reaction to form hydrated calcium silicate gel. The polyphosphate in the formula can form a stable complex with the magnesium ions in magnesium bicarbonate, thereby significantly improving the stability of magnesium ions in magnesium bicarbonate and ensuring the performance of magnesium bicarbonate.

[0041] Furthermore, although the carbonation of steel slag increases the Ca content of steel slag, 2+ and Mg 2+The dissolution degree of the artificial stone and the promotion of carbonation of steel slag and formation of hydrated calcium silicate gel by magnesium bicarbonate are beneficial to improving the strength of the artificial stone. However, when the strength is too high and the toughness is insufficient, the artificial stone is prone to break under the action of external force. Therefore, the technical solution also adds fiber to the artificial stone slurry formula. The fiber itself has excellent flexibility and can form a mesh structure inside the artificial stone, effectively dispersing and transmitting stress, reducing the concentrated stress points caused by external forces, thereby enhancing the flexibility and crack resistance of the artificial stone and ensuring the overall strength of the artificial stone.

[0042] Thirdly, due to the irregular particle size and shape of steel slag, and the fact that steel slag easily forms uneven crystals during the carbonation process, the surface of the artificial stone is relatively rough, affecting the aesthetics and use effect. Therefore, the technical solution also adds calcium carbonate whiskers to the raw material formula of the artificial stone slurry. As a fine needle-shaped material, calcium carbonate whiskers have a high aspect ratio and specific surface area. In the preparation process of artificial stone, they can not only effectively prevent crack expansion, which is beneficial to improving the crack resistance of artificial stone, but also can be used as crystal seeds to provide growth sites for calcium carbonate crystals and magnesium carbonate crystals produced by the carbonation of steel slag, forming a dense skeleton structure, thereby effectively overcoming the technical problem of the rough surface of artificial stone caused by the irregular particle size and shape of steel slag.

[0043] In addition, silica fume can be filled in the gaps between steel slag powder particles to improve density, and the calcium carbonate crystals, magnesium carbonate crystals, silica gel, hydrated magnesium silicate gel and hydrated calcium silicate gel generated during the reaction process can wrap the calcium and magnesium sand to form crystals, which can be filled in artificial stone, which is also conducive to improving the density of artificial stone. The above two aspects of improving density can enhance the fineness and smoothness of artificial stone. In addition, the polyphosphate in the formula can also guide the growth of the above crystals, making the artificial stone have a more uniform and dense microstructure, further ensuring the fineness and smoothness of artificial stone.

[0044] Finally, according to the weight percentage, the artificial stone slurry includes the following raw materials: 40-60 parts of steel slag, 70-120 parts of calcium magnesium sand, 1-5 parts of magnesium bicarbonate, 0.01-0.05 parts of calcium carbonate whisker, 0.01-0.03 parts of polyphosphate, 2-10 parts of silica fume, 1-2 parts of fiber and 8-10 parts of water. By controlling the addition amount of each component in the artificial stone slurry within a more preferred range, the performance of the artificial stone is better and meets the use requirements.

[0045] It should be noted that the steel slag may be converter slag, ladle slag, refined slag, etc., and the types thereof are not limited herein.

[0046] Further, the particle size of the steel slag is less than 75 μm, and the specific surface area is greater than 350 m 2 / g.

[0047] The smaller the particle size of the steel slag, the larger the specific surface area, which is more conducive to increasing the contact area between the steel slag and CO2, thereby increasing the degree of the steel slag carbonation reaction; at the same time, a smaller particle size and a larger specific surface area are also conducive to improving the fineness and smoothness of the surface of the artificial stone. However, when the particle size is further reduced and the specific surface area is increased, the improvement effect is limited and the production cost is easily increased. Therefore, in this technical solution, the particle size of the steel slag is limited to <75μm and the specific surface area is limited to >350m 2 / g, which is beneficial to improve the strength and surface smoothness of artificial stone at a lower cost.

[0048] It is further explained that, calculated by mass percentage, the chemical composition of the steel slag includes 12-14% silicon dioxide, 40-45% calcium oxide, 3-5% magnesium oxide, 3-5% aluminum oxide, 20-25% iron oxide, 4-6% manganese oxide, 1-2% titanium dioxide, 0-1% potassium oxide and 2-4% phosphorus pentoxide.

[0049] The present technical solution preferably adds steel slag having a calcium oxide content of 40-45% and a magnesium oxide content of 3-5% calculated by mass percentage to the artificial stone slurry formula, so that the total content of calcium oxide and magnesium oxide in the artificial stone slurry formula reaches 43-50%, which is beneficial to increase the carbonation degree of the steel slag, thereby promoting the improvement of the strength of the artificial stone.

[0050] Preferably, calculated by mass percentage, the chemical composition of the steel slag includes 13.8% silicon dioxide, 43.6% calcium oxide, 4.8% magnesium oxide, 4.1% aluminum oxide, 24.6% iron oxide, 5.2% manganese oxide, 1.1% titanium dioxide, 0.5% potassium oxide and 2.3% phosphorus pentoxide.

[0051] To further illustrate, the fibers include any one or more combinations of polypropylene fibers, polyethylene fibers, polyoxymethylene fibers and polyvinyl alcohol fibers.

[0052] Polypropylene fiber, polyethylene fiber, polyoxymethylene fiber and polyvinyl alcohol fiber all have high strength and high modulus. The above raw materials can be effectively dispersed in the slurry to form a three-dimensional network structure, thereby improving the overall strength and toughness of the artificial stone. In addition, polypropylene fiber and polyvinyl alcohol fiber also have good acid and alkali resistance and corrosion resistance, and can be applied to various environments. Therefore, the technical solution preferably includes any one or more combinations of polypropylene fiber, polyethylene fiber, polyoxymethylene fiber and polyvinyl alcohol fiber, which is not only conducive to improving the strength of the artificial stone, but also conducive to improving its durability.

[0053] Further description, calculated by mass percentage, the calcium-magnesium sand includes 0-30% of Class I sand of 26-40 mesh, 40-60% of Class II sand of 40-70 mesh, 15-30% of Class III sand of 70-120 mesh and 10-25% of Class IV sand of 120-200 mesh.

[0054] In the technical solution, the mesh size and proportion of various types of sand materials are optimized, which is beneficial to improving the density of artificial stone, thereby improving its strength and surface smoothness.

[0055] To further illustrate, the polyphosphate includes any one of sodium pyrophosphate, potassium pyrophosphate, sodium tripolyphosphate, potassium tripolyphosphate, sodium hexametaphosphate and potassium hexametaphosphate.

[0056] By preferably selecting a plurality of types of polyphosphate, it is possible to select suitable raw materials according to actual needs while ensuring the performance of artificial stone, thereby providing more possibilities and flexibility for its application.

[0057] It is further explained that the artificial stone slurry also includes a silane coupling agent;

[0058] Calculated by weight, the artificial stone slurry includes the following raw materials: 40-60 parts of steel slag, 70-120 parts of calcium magnesium sand, 1-5 parts of magnesium bicarbonate, 0.01-0.05 parts of calcium carbonate whiskers, 0.01-0.03 parts of polyphosphate, 2-10 parts of silica fume, 1-2 parts of fiber, 0.01-0.05 parts of silane coupling agent and 8-10 parts of water.

[0059] In the technical solution, a silane coupling agent is added to the artificial stone slurry to improve the interfacial bonding force between the fiber and other raw materials, thereby ensuring the effective distribution and enhancement effect of the fiber in the artificial stone.

[0060] Preferably, the silane coupling agent includes any one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.

[0061] A method for preparing a fine, smooth and high-strength artificial stone, which is used to prepare the fine, smooth and high-strength artificial stone, comprises the following steps:

[0062] A. dissolving a formula amount of magnesium bicarbonate, calcium carbonate whisker, silica fume and silane coupling agent in a part of the formula amount of water, and stirring evenly to obtain a first mixed material;

[0063] B. uniformly mixing the remaining amount of water and polyphosphate to obtain a second mixture;

[0064] C. After the first mixture, the second mixture, the formula amount of steel slag and calcium magnesium sand are mixed evenly, the formula amount of fiber is added, and the artificial stone slurry is obtained after stirring evenly;

[0065] D. Pour the artificial stone slurry into the mold and press it into shape to obtain the intermediate product;

[0066] E. The intermediate product is subjected to carbonation curing and then solidified to obtain a fine, smooth and high-strength artificial stone, wherein the thickness of the artificial stone is 10 to 40 mm, the compressive strength is ≥110 MPa, and the flexural strength is ≥19 MPa.

[0067] The technical solution also proposes a method for preparing a fine, smooth and high-strength artificial stone, which has simple steps and strong operability, and is conducive to ensuring the relevant properties of the artificial stone during the preparation process.

[0068] Specifically, the traditional artificial stone must be at least 90 mm to ensure the realization of the excellent performance of the artificial stone. If the artificial stone slurry of the present technical solution is used to prepare the artificial stone, its thickness only needs to reach 10 to 40 mm to achieve a compressive strength of ≥110 MPa and a flexural strength of ≥19 MPa, which greatly saves costs.

[0069] Among them, carbonation curing refers to sending the bricks into a carbonation curing box filled with CO2 gas for curing.

[0070] Further, in step E, the curing temperature of the carbonation curing is 20-90° C., the curing time is 1-72 h, the curing pressure is 0.1-0.4 MPa, and the purity of CO2 is 50-99.9%.

[0071] When the curing temperature, curing pressure and CO2 purity are too high, the carbonation rate will be too fast, the surface of the artificial stone will be densified too early, and the deep penetration of CO2 will be hindered; when the curing temperature, curing pressure and CO2 purity are too low, the reaction rate will be too slow, affecting the production efficiency. In order to improve the degree of carbonation reaction, the curing temperature of carbonation curing is specifically limited to 20-90°C, the curing pressure is limited to 0.1-0.4MPa, and the purity of CO2 is limited to 50-99.9%, ensuring that CO2 can fully penetrate into the interior of the artificial stone, improve the degree of carbonation reaction, ensure production efficiency and reduce production costs while ensuring the strength of the artificial stone.

[0072] Furthermore, when the curing time is insufficient, the carbonation degree will decrease; when the curing time is too long, the carbonation degree will not increase significantly, and the production efficiency will be easily reduced. Therefore, the technical solution limits the curing time to 1 to 72 hours, so as to improve the production efficiency while improving the carbonation degree and the strength of the artificial stone.

[0073] Further, in step D, the pressure of the pressing molding is 8 to 25 MPa.

[0074] When the pressure during the press molding process is too low, the artificial stone slurry cannot be fully compacted, resulting in more gaps and loose areas inside the artificial stone, which not only affects the fineness and smoothness of the artificial stone, but also reduces its overall strength; when the pressure of the press molding is too high, the fineness and smoothness and strength of the artificial stone are not significantly improved, and the production requirements are high, which is easy to increase the production cost. Therefore, the technical solution limits the pressure of the press molding to ensure its performance at a lower cost and higher production efficiency.

[0075] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0076] Example 1

[0077] In this embodiment, the artificial stone slurry includes the following raw materials calculated by weight: 40 parts of steel slag, 80 parts of calcium magnesium sand, 2 parts of magnesium bicarbonate, 0.03 parts of calcium carbonate whisker, 0.02 parts of sodium tripolyphosphate, 4 parts of silica fume, 1 part of polypropylene fiber and 8 parts of water; the particle size of the steel slag is 50 μm, and the specific surface area is 380 m 2 / g; calculated by mass percentage, the chemical composition of the steel slag includes 13.8% silicon dioxide, 43.6% calcium oxide, 4.8% magnesium oxide, 4.1% aluminum oxide, 24.6% iron oxide, 5.2% manganese oxide, 1.1% titanium dioxide, 0.5% potassium oxide and 2.3% phosphorus pentoxide; the mineral components of the steel slag include tricalcium silicate, β-type dicalcium silicate, γ-type dicalcium silicate, free calcium oxide and free magnesium oxide; calculated by mass percentage, the calcium-magnesium sand includes 15% of Class I sand of 26-40 mesh, 40% of Class II sand of 40-70 mesh, 25% of Class III sand of 70-120 mesh and 20% of Class IV sand of 120-200 mesh.

[0078] The method for preparing the fine, smooth and high-strength artificial stone in this embodiment comprises the following steps:

[0079] A. dissolving the formulated amount of magnesium bicarbonate, calcium carbonate whiskers and silica fume in 30% of the formulated amount of water, and stirring evenly to obtain a first mixed material;

[0080] B. Evenly mix 70% of the water in the formula with sodium tripolyphosphate to obtain a second mixture;

[0081] C. Evenly mix the first mixed material, the second mixed material, the formulated amount of steel slag, the first type of sand material of 26 to 40 meshes, the second type of sand material of 40 to 70 meshes, the third type of sand material of 70 to 120 meshes and the fourth type of sand material of 120 to 200 meshes, then add the formulated amount of polypropylene fiber, stir evenly to obtain the artificial stone slurry;

[0082] D. Pour the artificial stone slurry into the mold and press it under a pressure of 10MPa to obtain an intermediate product;

[0083] E. The intermediate product is subjected to carbonation curing at a curing temperature of 40°C, a curing time of 24h, a curing pressure of 0.3MPa, and a CO2 purity of 60%, and then solidified to obtain a fine, smooth and high-strength artificial stone.

[0084] Example 2

[0085] Calculated by weight, the artificial stone slurry includes the following raw materials: 50 parts of steel slag, 90 parts of calcium magnesium sand, 3 parts of magnesium bicarbonate, 0.02 parts of calcium carbonate whisker, 0.01 parts of sodium hexametaphosphate, 5 parts of silica fume, 2 parts of polyethylene fiber, 0.03 parts of γ-aminopropyl triethoxysilane and 8 parts of water; the particle size of the steel slag is 30μm, and the specific surface area is 400m 2 / g; calculated by mass percentage, the chemical composition of the steel slag includes 13.8% silicon dioxide, 43.6% calcium oxide, 4.8% magnesium oxide, 4.1% aluminum oxide, 24.6% iron oxide, 5.2% manganese oxide, 1.1% titanium dioxide, 0.5% potassium oxide and 2.3% phosphorus pentoxide; the mineral components of the steel slag include tricalcium silicate, β-type dicalcium silicate, γ-type dicalcium silicate, free calcium oxide and free magnesium oxide; calculated by mass percentage, the calcium-magnesium sand includes 10% of Class I sand of 26-40 mesh, 50% of Class II sand of 40-70 mesh, 15% of Class III sand of 70-120 mesh and 25% of Class IV sand of 120-200 mesh.

[0086] The method for preparing the fine, smooth and high-strength artificial stone in this embodiment comprises the following steps:

[0087] A. dissolving the formulated amount of magnesium bicarbonate, calcium carbonate whiskers, silica fume and γ-aminopropyltriethoxysilane in 40% of the formulated amount of water, and stirring evenly to obtain a first mixed material;

[0088] B. mixing 60% of the water in the formula with sodium hexametaphosphate to obtain a second mixture;

[0089] C. Evenly mix the first mixed material, the second mixed material, the formulated amount of steel slag, the first type of sand material of 26 to 40 meshes, the second type of sand material of 40 to 70 meshes, the third type of sand material of 70 to 120 meshes and the fourth type of sand material of 120 to 200 meshes, then add the formulated amount of polyethylene fiber, stir evenly to obtain the artificial stone slurry;

[0090] D. Pour the artificial stone slurry into the mold and press it under a pressure of 15MPa to obtain an intermediate product;

[0091] E. The intermediate product is subjected to carbonation curing at a curing temperature of 60°C, a curing time of 30 hours, a curing pressure of 0.2MPa, and a CO2 purity of 80%, and then solidified to obtain a fine, smooth and high-strength artificial stone.

[0092] Example 3

[0093] Calculated by weight, the artificial stone slurry includes the following raw materials: 60 parts of steel slag, 100 parts of calcium magnesium sand, 4 parts of magnesium bicarbonate, 0.04 parts of calcium carbonate whisker, 0.03 parts of potassium tripolyphosphate, 10 parts of silica fume, 2 parts of polyoxymethylene fiber, 0.05 parts of γ-glycidyloxypropyltrimethoxysilane and 10 parts of water; the particle size of the steel slag is 20μm, and the specific surface area is 420m 2 / g; calculated by mass percentage, the chemical composition of the steel slag includes 13.8% silicon dioxide, 43.6% calcium oxide, 4.8% magnesium oxide, 4.1% aluminum oxide, 24.6% iron oxide, 5.2% manganese oxide, 1.1% titanium dioxide, 0.5% potassium oxide and 2.3% phosphorus pentoxide; the mineral components of the steel slag include tricalcium silicate, β-type dicalcium silicate, γ-type dicalcium silicate, free calcium oxide and free magnesium oxide; calculated by mass percentage, the calcium-magnesium sand includes 30% of Class I sand of 26-40 mesh, 40% of Class II sand of 40-70 mesh, 15% of Class III sand of 70-120 mesh and 15% of Class IV sand of 120-200 mesh.

[0094] The method for preparing the fine, smooth and high-strength artificial stone in this embodiment comprises the following steps:

[0095] A. dissolving the formulated amount of magnesium bicarbonate, calcium carbonate whiskers, silica fume and γ-glycidyloxypropyltrimethoxysilane in 40% of the formulated amount of water, and stirring evenly to obtain a first mixed material;

[0096] B. Evenly mix 60% of the water in the formula with potassium tripolyphosphate to obtain a second mixture;

[0097] C. Evenly mix the first mixed material, the second mixed material, the formulated amount of steel slag, the first type of sand material of 26 to 40 meshes, the second type of sand material of 40 to 70 meshes, the third type of sand material of 70 to 120 meshes and the fourth type of sand material of 120 to 200 meshes, then add the formulated amount of polyoxymethylene fiber, stir evenly to obtain the artificial stone slurry;

[0098] D. Pour the artificial stone slurry into the mold and press it under a pressure of 20MPa to obtain an intermediate product;

[0099] E. The intermediate product is subjected to carbonation curing at a curing temperature of 70°C, a curing time of 48h, a curing pressure of 0.1MPa, and a CO2 purity of 50%, and then solidified to obtain a fine, smooth and high-strength artificial stone.

[0100] Comparative Example 1

[0101] The preparation method and raw materials of Comparative Example 1 are the same as those of Example 2, except that no steel slag is added to the artificial stone slurry formula in Comparative Example 1.

[0102] Comparative Example 2

[0103] The preparation method and raw materials of Comparative Example 2 are the same as those of Example 2, except that no polyphosphate is added to the artificial stone slurry formula in Comparative Example 2.

[0104] Comparative Example 3

[0105] The preparation method and raw materials of Comparative Example 3 are the same as those of Example 2, except that magnesium bicarbonate is not added to the artificial stone slurry formula in Comparative Example 3.

[0106] Comparative Example 4

[0107] The preparation method and raw materials of Comparative Example 4 are the same as those of Example 2, except that no silica fume is added to the artificial stone slurry formula in Comparative Example 4.

[0108] Comparative Example 5

[0109] The preparation method and raw materials of Comparative Example 5 are the same as those of Example 2, except that no calcium carbonate whiskers are added to the artificial stone slurry formula in Comparative Example 5.

[0110] Artificial stones were prepared by the preparation methods in the above embodiments and comparative examples, respectively. The thickness of the artificial stones was measured using a vernier caliper. The flexural strength and compressive strength of the artificial stones were tested using the test standard of "GB / T 35160 Test Methods for Synthetic Stones". The surface of the artificial stones was observed with the naked eye, and the results are shown in Table 1 below.

[0111] Table 1 Test results of relevant properties of artificial stone

[0112] Experiment number Appearance Thickness(mm) Compressive strength(MPa) Flexural strength(MPa) Example 1 Delicate and smooth surface 30.69 110.69 19.23 Example 2 Delicate and smooth surface 30.24 112.35 20.47 Example 3 Delicate and smooth surface 29.91 111.76 20.18 Comparative Example 1 Delicate and smooth surface 30.30 89.31 15.74 Comparative Example 2 Rough surface 30.45 92.44 16.40 Comparative Example 3 Slightly rough surface 30.18 88.61 14.69 Comparative Example 4 Slightly rough surface 30.27 87.54 14.50 Comparative Example 5 Rough surface 30.22 105.42 17.52

[0113] From the performance test results in Table 1, it can be seen that the technical solution provides a fine, smooth and high-strength artificial stone with a compressive strength of ≥110MPa and a flexural strength of ≥19MPa. It not only has a fine and smooth surface, but also has high strength, which meets the use requirements.

[0114] In Comparative Example 1, since no steel slag is added, the strength of the artificial stone slurry is deteriorated, thereby affecting the strength of the artificial stone.

[0115] Comparative Example 2: Since no polyphosphate was added, the Ca content in the steel slag was 2+ and Mg 2+The degree of participation in the carbonation reaction is limited, resulting in insufficient carbonation of the steel slag, thus affecting the strength of the artificial stone. In addition, the failure to add polyphosphate will cause magnesium bicarbonate to be unable to exist stably, decompose to form magnesium carbonate precipitate and magnesium hydroxide precipitate, and reduce the concentration of magnesium ions and bicarbonate ions in the solution. The reduction in magnesium ion concentration is not conducive to the formation of hydrated magnesium silicate gel, and the reduction in bicarbonate ion concentration is not conducive to improving the carbonation degree of steel slag. The above two aspects also affect the strength of artificial stone. In addition, the failure to add polyphosphate also results in the inability to guide the growth of crystals, affecting the fineness and smoothness of artificial stone.

[0116] In Comparative Example 3, since magnesium bicarbonate was not added, magnesium bicarbonate and silica fume could not be used to generate hydrated magnesium silicate gel, which affected the strength and fine smoothness of the artificial stone. In addition, the absence of magnesium bicarbonate increased the concentration of bicarbonate ions, reducing the carbonation degree of the slag, which also affected the strength and fine smoothness of the artificial stone.

[0117] In Comparative Example 4, since no silica fume is added, magnesium bicarbonate and silica fume cannot be used to generate hydrated magnesium silicate gel, thereby affecting the strength and fine smoothness of the artificial stone. In addition, without the addition of silica fume, calcium hydroxide generated by the reaction of silica fume with free calcium oxide, tricalcium silicate, β-type dicalcium silicate and γ-type dicalcium silicate in the steel slag in an aqueous environment cannot be used to generate hydrated calcium silicate gel, and magnesium hydroxide generated by the reaction of silica fume with free magnesium oxide in an aqueous environment cannot be used to generate hydrated magnesium silicate gel, resulting in reduced strength and fine smoothness of the artificial stone.

[0118] Since no calcium carbonate whiskers were added to Comparative Example 5, it was unable to fill the voids of the artificial stone, prevent the cracks from expanding, and provide growth sites for calcium carbonate and magnesium carbonate produced by the carbonation of steel slag, thereby affecting the strength and fine smoothness of the artificial stone.

[0119] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.

Claims

1. A fine, smooth and high-strength artificial stone, characterized in that: Obtained by carbonation, curing and solidification of artificial stone slurry; Calculated by weight, the artificial stone slurry includes the following raw materials: 40-60 parts of steel slag, 70-120 parts of calcium magnesium sand, 1-5 parts of magnesium bicarbonate, 0.01-0.05 parts of calcium carbonate whiskers, 0.01-0.03 parts of polyphosphate, 2-10 parts of silica fume, 1-2 parts of fiber and 8-10 parts of water; The chemical components of the steel slag include silicon dioxide, magnesium oxide and calcium oxide; the mineral components of the steel slag include tricalcium silicate, beta-type dicalcium silicate, gamma-type dicalcium silicate, free calcium oxide and free magnesium oxide.

2. The fine, smooth and high-strength artificial stone according to claim 1, characterized in that: The particle size of the steel slag is less than 75 μm, and the specific surface area is greater than 350 m 2 / g.

3. The fine, smooth and high-strength artificial stone according to claim 1, characterized in that: Calculated by mass percentage, the chemical composition of the steel slag includes 12-14% silicon dioxide, 40-45% calcium oxide, 3-5% magnesium oxide, 3-5% aluminum oxide, 20-25% iron oxide, 4-6% manganese oxide, 1-2% titanium dioxide, 0-1% potassium oxide and 2-4% phosphorus pentoxide.

4. The fine, smooth and high-strength artificial stone according to claim 1, characterized in that: The fibers include any one or more combinations of polypropylene fibers, polyethylene fibers, polyoxymethylene fibers and polyvinyl alcohol fibers.

5. The fine, smooth and high-strength artificial stone according to claim 1, characterized in that: Calculated by mass percentage, the calcium-magnesium sand includes 0-30% of Class I sand of 26-40 meshes, 40-60% of Class II sand of 40-70 meshes, 15-30% of Class III sand of 70-120 meshes and 10-25% of Class IV sand of 120-200 meshes.

6. The fine, smooth and high-strength artificial stone according to claim 1, characterized in that: The polyphosphate includes any one of sodium pyrophosphate, potassium pyrophosphate, sodium tripolyphosphate, potassium tripolyphosphate, sodium hexametaphosphate and potassium hexametaphosphate.

7. The fine, smooth and high-strength artificial stone according to claim 1, characterized in that: The artificial stone slurry also includes a silane coupling agent; Calculated by weight, the artificial stone slurry includes the following raw materials: 40-60 parts of steel slag, 70-120 parts of calcium magnesium sand, 1-5 parts of magnesium bicarbonate, 0.01-0.05 parts of calcium carbonate whiskers, 0.01-0.03 parts of polyphosphate, 2-10 parts of silica fume, 1-2 parts of fiber, 0.01-0.05 parts of silane coupling agent and 8-10 parts of water.

8. A method for preparing a fine, smooth and high-strength artificial stone, characterized in that: The method for preparing the fine, smooth and high-strength artificial stone as claimed in claim 7 comprises the following steps: A. dissolving a formula amount of magnesium bicarbonate, calcium carbonate whisker, silica fume and silane coupling agent in a part of the formula amount of water, and stirring evenly to obtain a first mixed material; B. uniformly mixing the remaining amount of water and polyphosphate to obtain a second mixture; C. After the first mixture, the second mixture, the formula amount of steel slag and calcium magnesium sand are mixed evenly, the formula amount of fiber is added, and the artificial stone slurry is obtained after stirring evenly; D. Pour the artificial stone slurry into the mold and press it into shape to obtain the intermediate product; E. The intermediate product is subjected to carbonation curing and then solidified to obtain a fine, smooth and high-strength artificial stone, wherein the thickness of the artificial stone is 10 to 40 mm, the compressive strength is ≥110 MPa, and the flexural strength is ≥19 MPa.

9. The method for preparing a fine, smooth and high-strength artificial stone according to claim 8, characterized in that: In step E, the carbonation curing temperature is 20-90° C., the curing time is 1-72 h, the curing pressure is 0.1-0.4 MPa, and the purity of CO2 is 50-99.9%.

10. The method for preparing a fine, smooth and high-strength artificial stone according to claim 8, characterized in that: In step D, the pressure of the compression molding is 8 to 25 MPa.